The Role of The Organization Of Islamic Cooperation (OIC) in Strengthening Islamic Diplomacy And Conflict Resolution - Munandar, Aris; Umar Lubis, Amany Burhanuddin; Faiqoh, Fadhilah; Susanti, Endang (ARMADA : Jurnal Penelitian Multidisiplin, 2025)
This research aims to analyze the concept and implementation of Islamic diplomacy as an alternative paradigm in global conflict resolution. Islamic diplomacy departs from the ethical principles of the Qur'an such as 'adl (justice), sulḥ (peace), ṣidq (honesty), and rahmah (compassion) which place morality at the core of relations between countries. Through a library research approach, this study examines classical and contemporary literature on international relations theory, Islamic political thought, and the diplomatic practices of Islamic world institutions such as the Organization of Islamic Cooperation (OIC) and the Arab League. The results of the study show that Islamic diplomacy is not just a political instrument, but a value system that serves to build global justice and sustainable peace. In the modern context, Islamic diplomacy can be actualized through a model  of clean diplomacy that is free from narrow interests, political manipulation, and power hegemony. This reactualization includes the integration of Islamic values in foreign policy, strengthening the role of Islamic multilateral institutions, and ethics-based digital diplomacy. In conclusion, Islamic diplomacy offers a moral and spiritual paradigm that is able to correct the ethical void in conventional diplomacy and become the foundation for a peaceful, just, and civilized world order